Human Resource Management in Health Care: A Case of Turnover in Long term care - Fuqua, Ronald M.; Walden, Latrina; Smith, Kendolyn (Advances in Social Sciences Research Journal, 2018)
The management of human resources in long term health care is challenging. Whether it is home care, skilled nursing care, hospice care, rehabilitation, case management, medical supply, or pharmacy, the work force consists of skilled, licensed professionals. In a case study of a vertically integrated long term care organization operating in several states, the turnover rates for various positions and types of organization were calculated and analyzed. The results point to acuity level, type of long term care provider, and the possibility of low pay as factors for turnover rates from an acceptable level to extremely high and unacceptable levels.